THE METAPHOR ANALYSIS OF DANIEL CAESAR’S SONG LYRICS - Fitri Apriyanti; Faisal Zarkashi Arif (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2024)
The Metaphor Analysis of Daniel Caesar''s Song is a research study that examines the meaning and type of metaphorical language contained in Daniel Caesar''s song lyrics. Metaphors are ideas to discuss something, give an understanding of the world, and are used by poets, songwriters, and book writers to convey meaning in an interesting way. The aim of this research is to provide understanding, enhance knowledge, add new experiences, and fill gaps. Qualitative research aims to understand phenomena experienced by research subjects, while descriptive research collects descriptive data and presents it in reports and descriptions. The researcher found 8 structural metaphors (53%), 3 orientation metaphors (20%), and 4 ontological metaphors (27%). According to conceptual metaphor, the most dominant type of metaphor is structural metaphor. Daniel Caesar''s songs are composed of words taken from poems and given additional melodies to create attraction. This research can be used as a reference source for the study of metaphoric language and its various meanings. Institutions can benefit by providing better support and making it easier for students to access resources related to metaphoric languages.